Digital-based cash waqf behavioral scale: A Maqasid approach - Hanudin Amin; Faizah Panggi (Emerald, 2025)
This study introduced the Digital-Based Cash Waqf Behavioral Scale (Depascale) to examine the behavioral patterns of waqifs in Malaysia. The scale is structured around four key constructs: Perceived Educational Programma (PEP), Perceived Justice (PJ), Perceived Welfare (PW) and Perceived Institutional Effectiveness (PIE). Design/methodology/approach – Depascale was developed based on the Maqasid al-Shariah framework and its applicability was empirically tested among 1,025 waqifs using SPSS version 26. Findings – Depascale demonstrated acceptable levels of validity, reliability, correlation and generalizability. Among its constructs, PW recorded the highest mean index score (1.1990), whereas PJ registered the lowest (1.0340). Research limitations/implications – The scope of the findings was limited by the selected geographical areas, the specific sample population and the technological settings employed in the study. Practical implications – By utilizing Depascale, waqf institutions can strengthen cash waqf behavior among waqifs, thereby promoting sustained contributions and ensuring the long-term sustainability of cash waqf initiatives. Originality/value – This study introduced the newly developed Depascale to Analyse waqif cash waqf contributions within the Malaysian context.